2018
DOI: 10.1037/stl0000126
|View full text |Cite
|
Sign up to set email alerts
|

Interteaching in an asynchronous online class.

Abstract: The present study investigated the effectiveness of interteaching versus traditional lecture-based teaching in two 9-week online asynchronous classes. Participants were undergraduate students enrolled in one of two sections of a psychology of learning course (N ϭ 62). The study used an alternating-treatments design, switching between interteaching and lecture-based teaching throughout the term. Type of instruction was counterbalanced across sections, so that material taught using interteaching in one section w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 18 publications
(38 reference statements)
7
18
1
Order By: Relevance
“…Therefore, each week students (a) submitted answers to a 30-question prep guide, (b) discussed prep guide questions in groups on an asynchronous written discussion board, (c) uploaded a record sheet, and (d) watched a brief clarifying lecture delivered via PowerPoint on a weekly basis. For additional details on the interteaching components of this study, see Gayman et al ( 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, each week students (a) submitted answers to a 30-question prep guide, (b) discussed prep guide questions in groups on an asynchronous written discussion board, (c) uploaded a record sheet, and (d) watched a brief clarifying lecture delivered via PowerPoint on a weekly basis. For additional details on the interteaching components of this study, see Gayman et al ( 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…One teaching method accumulating a growing body of empirical evidence supporting its efficacy is interteaching. Interteaching is a relatively new behavioral approach to college instruction in which contingencies are arranged in support of frequent student engagement and peer-to-peer collaboration, and lectures are reduced to a supportive, supplementary role (Gayman et al, 2018 , 2020 ). In addition to producing better learning outcomes (for reviews, see Hurtado-Parrado et al, 2021 ; Querol et al, 2015 ; Saville et al, 2011 ; Sturmey et al, 2015 ), students have reported interteaching to be more enjoyable (Querol et al, 2015 ; Saville et al, 2011 ), and interteaching has been shown to improve long-term retention (Felderman, 2014 ; Saville et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though interteaching relies on peer interactions, at least three empirical studies have demonstrated that it can be effective in an online learning environment (Gayman et al 2018;Rieken et al 2018;Soldner et al 2017). For example, Gayman et al evaluated effects of interteaching on undergraduate student performance and retention in an asynchronous online class.…”
Section: Interteachingmentioning
confidence: 99%
“…For example, in the Fall of 2017, at least 34% (6.6 million out of 19 million) of students enrolled at degree-granting postsecondary institutions had taken an online course (United States Department of Education 2018). Further, enrollment in online classes has been increasing and even outpaced overall enrollment in higher education Seaman 2010, 2013) and there have been numerous descriptive and experimental studies examining online pedagogy (Blackman et al 2020;Crawford-Ferre and West 2012;Gayman et al 2018;Heinicke et al 2017;Kentnor 2015;Malkin et al 2018;Rieken et al 2018;Rios et al 2018;Sieber 2005;Watts 2016). In a recent review, Sun and Chen (2016) summarized some key design factors that need to be considered to make online instruction effective.…”
mentioning
confidence: 99%